Diversity of arbuscular mycorrhizal fungi in asphalt post-mining land in Buton Island, Indonesia - FAISAL DANU TUHETERU; HUSNA HUSNA; ALBASRI ALBASRI; HENI MANGUN EFFENDY; ASRIANTI ARIF; BASRUDIN BASRUDIN; EDY JAMAL TUHETERU; SRI MULYONO; RAGIL SB IRIANTO (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Tuheteru FD, Husna, Albasri, Effendy HM, Arif A, Basrudin, Tuheteru EJ, Mulyono S, Irianto RSB. 2022. Diversity of arbuscular mycorrhizal fungi in asphalt post-mining land in Buton Island, Indonesia. Biodiversitas 23: 6327-6334. Studies on the presence and diversity of Arbuscular Mycorrhizal Fungi (AMF) on overburden (OB) and asphalt post-mining areas in Buton Island are still limited. The purpose of this study was to examine the presence and diversity of AMF on OB and asphalt post-mining stockpiles in Buton Island, Southeast Sulawesi Province. The sampling of soil and roots of successional plants was carried out at eight post-mining sites at the IUP Kabungka (Pasarwajo) (6 sites) PT. WIKA Aspal and IUP Lawele (2 sites), PT. WIKA Bitumen. The AMF spores were isolated using the wet filter pour method, followed by the identification of AMF which was done by observing the morphology of AMF spores. The results showed that all successional plants were in symbiosis with AMF, which was indicated by the existence of AMF structure in plant roots with the percentage of AMF colonization ranging from 5 - 95%. The number of spores per 50 g ranged from 1 to 9 spores. A total of 9 AMF species were found to belong to five genera, i.e., Claroideoglomus, Haloatospora, Glomus, Gigaspora, and Cetraspora from three families. Claroideoglomus claroideum was found to be the most dominant species isolated with the high occurrence and the highest Importance and Shannon-Wiener Diversity Indices followed by Haloatospora cf. pansihalos, Glomus sp. 5, and Glomus sp. 4. This study also showed that the AMF diversity index differed among locations. The presence of AMF can accelerate the emergence and development of adaptive plants on post-asphalt mining land in Buton Island.